SOCIAL INNOVATION IN THE CULTURAL SECTOR: THE CASE OF PJE/PRODIGIUM - Saldanha, Fabio Prado; Delgado, Natalia Aguilar; Pozzebon, Marlei (Revista Brasileira de Casos de Ensino em Administração, 2021)
This case examines the major challenges faced by Productions Jeun’Est (PJE) and Prodigium, a social enterprise working in the cultural sector. The profits generated by Prodigium’s activities in the entertainment field are invested in the PJE training program that aims to increase the social inclusion of vulnerable youth by training them to be technicians in the cultural market. By studying this case, students are expected to understand the elements of a social business model, to analyze the role of the different elements forming a social innovation and to evaluate the challenges of planning its transfer to another context.